Parathyroid Neuroendocrine Tumor Located in the Trachea of one Bitch - Galeno, Lygia Silva; Barbalho Lima, Tiago; Santos de Jesus, Lucas Magno; de Andrade Oliveira Cruz, Thais Nascimento; Azevedo Carvalho, Victor Hugo; Costa Araújo Dourado, Adriana Vivian (Acta Scientiae Veterinariae, 2025)
Background: Neuroendocrine tumors make up a family of neoplasms that can be found in different tissues and organs, including those that do not usually contain neuroendocrine cells. These tumors are diagnosed based on histopathological examination and the presence of neuroendocrine markers in the immunohistochemical examination, including neuron-specific enolase (NSE), chromogranin A and synaptophysin. This paper describes the occurrence of a parathyroid neuroendocrine tumor located in the lumen of the trachea of one bitch, and characterizes its clinical evolution. Case: A 10-year-old bitch of Siberian Husky breed, suffering for a week from reported symptoms of coughing and dyspnea, was treated at the private Veterinary Hospital Petmania, São Luís, MA, Brazil. After a clinical evaluation, additional tests were requested, including a chest X-ray, complete blood count, assessment of renal (urea, creatinine) and liver function (albumin, ALT, AST, alkaline phosphatase), and abdominal ultrasound, all of which fell within the normal limits. The chest X-ray revealed a 2.1 cm x 1.2 cm formation in the region of the thoracic trachea. An electrocardiogram was performed, but revealed no changes. The patient underwent a tracheoscopy for excisional biopsy of the mass, using a polyp forceps. The biopsy material was subjected to histopathological and immunohistochemical analysis, which confirmed that it was a parathyroid neuroendocrine tumor containing immunoreactive neuron-specific enolase and calcitonin. A chest tomography was requested, but was not performed. After a parathyroid neuroendocrine tumor was diagnosed, additional complementary tests were carried out to examine changes in the thyroid and parathyroid, which included measurement of ionized calcium, post-dialysis free T4, total T4, sodium, chlorine, potassium and cervical ultrasound. These tests indicated mild hypercalcemia and hyponatremia. The patient was monitored clinically for 30 days, after which the symptoms of dyspnea and cough returned. The patient was subjected to tracheoscopy, which revealed a new tumor growth in the same location. Soon thereafter, the patient died. Discussion: Parathyroid neuroendocrine tumors are rare in dogs, and no reports were found of this type of neoplasm located in the trachea. The patient in this case report presented a mass in the intraluminal portion of the thoracic trachea, which led to the manifestation of respiratory obstruction. Neuroendocrine tumors may develop in tissues that do not contain neuroendocrine cells, such as the trachea. Furthermore, malignant neoplasms have the characteristic of inducing the dissemination of tumor cells that can implant themselves in other tissues, although no neoplastic lesion was found other than in the trachea in the patient of this case report. The treatment of tracheal neoplasms involves surgical resection and tracheal anastomosis. However, this is a complex surgical procedure, especially if it involves the intrathoracic trachea. In this patient, no surgical treatment was performed due to the rapid evolution of the disease and the lack of tomographic diagnosis for adequate surgical planning. Neuroendocrine tumors, albeit rare, have been described before in different anatomical locations in dogs. It is concluded that the neuroendocrine tumor of the patient in this case demonstrated an aggressive evolution with a poor prognosis and low survival rate after diagnosis. Keywords: tracheal tumors, neuron-specific enolase, calcitonin. Título: Tumor neuroendócrino de paratireóide localizado na traqueia de uma cadela Descritores: tumor traqueal, neuro enolase específica, calcitonina.